234k views
4 votes
Factor completely 2x^2+2x-24

User NewBike
by
4.8k points

2 Answers

3 votes

Answer:

2(x + 4)(x - 3)

Explanation:

Given

2x² + 2x - 24 ← factor out 2 from each term

= 2(x² + x - 12)

To factor the quadratic

Consider the factors of the constant term (- 12) which sum to give the coefficient of the x- term (+ 1)

The factors are + 4 and - 3, since

4 × - 3 = - 12 and 4 - 3 = + 1, thus

x² + x - 12 = (x + 4)(x - 3) and

2x² + 2x - 24 = 2(x + 4)(x - 3)

User VerizonW
by
6.3k points
2 votes

Answer:

2(x + 4)(x − 3)

Explanation:

Hope it helped you

User Lkopo
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.